Real-time detection of hepatitis B surface antigen using a hybrid graphene-gold nanoparticle biosensor - Ffion Walters (2D Materials, 2020)
A hybrid biosensor based on a graphene resistor functionalized with self-assembled Graphene-AuNPs (Gold Nanoparticles) is demonstrated for the real-time detection of hepatitis B surface antigen (HBsAg). The hybrid biosensor consists of a ssDNA sequence attached to a graphene resistor device via π–π stacking interactions in combination with a ssDNA functionalized AuNP. The ssDNA has complementary sequences which through hybridization, yield the graphene-AuNP hybrid biosensor. Real-time 2-point resistance measurements, performed using varying concentrations of HBsAg, show a linear dependence of resistance change against the logarithm of HBsAg concentration (log[HBsAg]). A limit of detection of 50 pg ml−1 was observed. Moreover, the hybrid biosensor platform has potential to be applied to any biomarker of interest.